Preparation of isolated and hydrolyzed proteins from rice bran and study of their chemical composition and antioxidant capacity - A. J. Al-Fatlawi,; M.A.Mousa, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The present study aimed to prepare isolated and hydrolyzed proteins from Iraqi rice bran variety Amber 33 and study the antioxidant capacity. The results of chemical analysis of moisture, protein, fat, ash, and carbohydrates showed that they reached 8.41, 12.85, 18.39, 6.28, and 54.07% respectively for whole rice bran and 9.54, 18.20, 2.16, 9.14, 60.96% respectively for defatted bran and 3.21, 84.69, 1.3, 7.43, 3.54% respectively for isolated protein. The degree of degradation was observed to increase with the progression of degradation time and the HRBPI7 degradant achieved the highest degree of degradation reaching 34.73% after 120 minutes without the appearance of a bitter taste, the free radical inhibition capacity reached 51.72% outperforming all other degradation treatments while the RBPI protein isolate achieved a free radical inhibition capacity of 49.63% compared to what the synthetic antioxidant BHT achieved, which recorded a free radical inhibition capacity of 72.89%. The HRBPI7 degradant achieved a reducing power capacity of 49.86% outperforming all other degradation treatments and close to what the RBPI protein isolate achieved in terms of reducing power capacity, which reached 48.86% compared to what the synthetic antioxidant BHT achieved, which recorded a reducing power capacity of 63.89%. The HRBPI7 hydrolysate achieved a ferrous ion binding capacity of 61.06%, outperforming all other hydrolysis treatments and approaching the ferrous ion binding capacity achieved by the RBPI protein isolate, which reached 52.22%, compared to the synthetic antioxidant BHT, which recorded a ferrous ion binding capacity of 71.83%.